Scoliosis Correction Surgery in Collagen Type VI Dysfunction - Babak Mirzashahi; Furqan Mohammed Yaseen Khan; Rasul Gharakhan Maleki; Mahdi Heshmatifar (Journal of Orthopedic and Spine Trauma, 2020)
Background: Collagen VI (COLVI) dysfunction results in a combination of connective tissue and muscular disorders. Spinal involvement and development of scoliosis precede loss of ambulation and respiratory deterioration in these patients. Therefore, spinal deformity correction surgery is warranted to preserve ambulation and respiratory function. Case Presentation: A twelve-year-old girl presented with progressive scoliosis accompanying respiratory deterioration, sitting imbalance, and wheelchair-bound. The patient demonstrated an array of overlapping phenotypes related to COLVI dysfunction, including developmental delay, muscular dystrophy (MD), fatty replacement of skeletal muscles, and reduced bone mineral density to mention few. Patient was diagnosed with COLVI dysfunction caused by COLVI alpha 2 (COL6A2) gene mutation. She had severe phenotype expression similar to Ullrich congenital MD (UCMD). A Cobb angle of 85 degrees and thoracic kyphosis of 40 degrees were recorded. Surgical correction was performed in the form of spinal fusion from T4 to S1 in addition to multiple level vertebral osteotomies. Conclusions: Respiratory distress and ambulatory problems are life-endangering events in these patients. As the disease progresses and respiratory distress increases, anesthesia becomes more difficult and the risk of surgery increases. Therefore, early intervention for correction of scoliosis is warranted to support the quality of life. Surgical time has to be kept as short as possible to minimize blood loss in these patients.